ANALYSIS OF CAUSES FOR PRE-DONATION DEFERRAL AMONG VOLUNTARY BLOOD DONORS AT A TERTIARY CARE HOSPITAL - S, SARAVANAN; SA, MANIMALA; M, PARIMALAM; RAVISHANKAR, JEYARAJ (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Pre-donation screening of potential blood donors is critical for ensuring the safety of the blood collected, and donor deferral as a result of risk factors is practiced worldwide. It is important to study the pattern of deferrals to reduce unnecessary deferrals and encourage continuous blood donation. The aim of the present study was to determine the rate and reasons for pre-donation donor deferral among voluntary blood donors. Methods: This was a single-center, retrospective cross-sectional study conducted by analyzing 3 years of data, from January 2020 to December 2022, over a period of 2 months (December 2022 and January 2023) retrieved from the donor deferral register. The data was entered in Microsoft Excel and analyzed using the Statistical Package for the Social Sciences software. Descriptive statistical measures were utilized to present the data. Results: Among 29,847 voluntary donors, 13.81% (4123/29,847) were deferred, of whom 84.2% (3472/4123) were males. The deferral rate among males was 12.19% (3472/28,480), while it was 47.62% (651/1367) in females. 53.04% of the deferred donors were in the age group of 18–30 years (2187/4123). 98.73% (4071/4123) of the deferrals were temporary. Hypothyroidism on treatment (42.30%, 22/52), uncontrolled diabetes on insulin (34.62%, 18/52), and epilepsy on treatment (11.54%, 6/52) were the common reasons for permanent deferral, while low hemoglobin (13.07%, 532/4,123), medications (11.67%, 475/4,071), and body piercing (9.85%, 406/4,123) were the most common reasons for temporary deferral. Low hemoglobin was the common reason for deferral among repeat donors (55.45%, 295/532) compared to first-time donors. Conclusion: The current findings suggest that it is important to increase awareness of voluntary, non-remunerated blood donation among young people and educate people about the common criteria for a healthy donor to minimize the loss of blood donors.